Kecenderungan Perilaku Narsistik pada Remaja Putri Pengguna Instagram - Wibowo, Wasis Purwo; Arnani, Ni Putu Rizky; Rini, Hapsari Puspita (JOURNAL OF EDUCATION FOR ALL, 2023)
The purpose of this study was to find out the narcissistic picture of young women who use Instagram. Instagram is a social media that can share all activities in the form of photos, videos and words. Narcissistic behavior is behavior that tends to pride itself excessively in order to gain recognition from others. The research method uses descriptive qualitative related to understanding the tendency of narcissistic behavior through Instagram social media. Participants are 18-year-old high school (SMA) girls. The results showed that the tendency of narcissistic behavior for young women who use Instagram, namely likes to upload photos and videos of themselves, shows a good impression and image in cyberspace, is proud and happy when they have lots of likes and followers, shows feeling superior, participants feel if they are attractive compared to their friends. friend, sensitive to criticism. There are factors that can contribute to the behavior of narcissistic tendencies, including lack of attention, influence of friends, frequency of using social media, the desire to show existence.